Development of E-Learning Chemistry Learning in SMA / MA Project Based Learning on Colloid Material with the Flipped Classroom Approach in Class XI Senior High School - Dollamulyana Harnas; Denny Mulyani Harnas; Toni Rizky Riyanov (Center For Advanced Material Processing, Artificial Intelligence, Biophys-Informatics (CAMPBIOTICS), Universitas Negeri Padang, 2021)
Abstract - This research was conducted to develop e-learning content using Moodle in chemistry subject, colloid material. This research is a Research and Development (R&D). Using the 4-D model with define, design, develop and disseminate stages. This research stage is only limited to the develop stage. The number of validators for this study was 3 validators. The results of the validation questionnaire will be analyzed using Cohen's kappa formula.